A 'movement for improvement'? A qualitative study of the adoption of social movement strategies in the implementation of a quality improvement campaign. Issue 7 (21st June 2017) - Waring, Justin; Crompton, Amanda
Abstract: Given the difficulties of implementing 'top‐down' quality improvements, health service leaders have turned to methods that empower clinicians to co‐produce 'bottom‐up' improvements. This has involved the adoption of strategies and activities associated with social movements, with clinicians encouraged to participate in collective action towards the shared goal of improvement. This paper examines the adoption of social movement methods by hospital managers as a strategy for implementing a quality improvement 'campaign'. Our case study suggests that, despite the claim of empowering clinicians to develop 'bottom‐up' improvements, the use of social movement methods can be more narrowly concerned with engaging clinicians in pre‐determined programmes of 'top‐down' change. It finds a prominent role for 'hybrid' clinical leaders and other staff representatives in the mobilisation of the campaign, especially for enrolling clinicians in change activities. The work of these 'hybrids' suggests some degree of creative mediation between clinical and managerial interests, but more often alignment with the aspirations of management. The study raises questions about the translation of social movement's theories as a strategy for managing change and re‐inventing professionalism.